Coaching Caregiver: Aplikasi Telehealth Berbasis Edukasi dan Konsultasi Kepada Caregiver Pasien Skizofrenia - Ni Made Wini Jayesthiwi Wanami Putri; Rovie Hikari Parastan; I Kadek Wahyu Putra Dyatmika; Cokorda Bagus Jaya Lesmana (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
Schizophrenia is a serious concern in psychiatric problem around the world. In 2018, this disorder has affecting 6.7 per 1000 incidence in Indonesia. Pharmacology and non-pharmacology treatment are recommended treatment for schizophrenia, those treatments will run effectively by supports from their family caregiver. Nowadays, family play an important role in caregiving schizophrenia patients. However, the recent status quo stated that not all caregiver understands how to take care the patients in a proper way. So that, caregiver need some education and other information to understand the schizophrenia patient. Based on Ozkan and Khatri research, providing psychoeducation data via technology (telehealth) to the family caregiver shows a positive and significant result. In reducing family caregiver burden of the patients with schizophrenia, Coaching Caregiver is an innovation to train family caregiver in taking care their family. Some aspects in this program based on DSM V and PPDGJ III such as education, consultation and decision support, psychosocial and behaviour therapy, social support, and monitoring that needed by a caregiver. Using a technology-based approach, this application expected to provide and encourage health services to reach a wider community. In addition, it is expected to reduce the burden of family caregiver in taking care their relatives/family.